THE UTILIZATION OF YOUTUBE FOR EXTENSIVE LISTENING: VOICES FROM THE LECTURERS AND STUDENTS - Sava Farhan Sila; Muhammad Handi Gunawan (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
The English language continues to be the most used language in the world. Learning it involves four crucial skills, with listening being one of the most vital. In the past, listening was commonly taught with conventional media such as CDs or audio cassettes. While valuable, these materials lacked interactivity, diversity, and adaptability to students’ needs. With the rise of online platforms, YouTube has emerged as a widely accessible and engaging medium for enhancing listening skills through extensive listening (EL) practices. Despite its growing use, existing studies mostly explored students’ perceptions, with few including lecturer perspectives. Therefore, this study aims to explore the views of students and a lecturer regarding the use of YouTube in EL to gain a deeper understanding of its implementation. A qualitative design with a case study approach was employed at a public university in Bandung, Indonesia. Participants included twenty-eight final-semester English Education students and a listening course lecturer. An open-ended questionnaire was used to obtain data on participants’ experiences using YouTube in EL. The data were analysed using NVivo, which helped organize and find recurring themes related to their perceptions. The results showed that both students and the lecturer had positive views of YouTube in EL. Participants praised its accessibility, content diversity, flexibility, and features that supported their learning needs. However, students also faced challenges such as internet issues, advertisements, and difficulty understanding unfamiliar accents. Despite this, they devised strategies to overcome these obstacles. The lecturer meanwhile, reported having minimal difficulty in recommending YouTube content for EL practice. These findings offer insights into YouTube’s role as a tool in extensive listening.